Comparisons of hunger across states: India State Hunger Index - Menon, Purnima; Deolalikar, Anil B.; Bhaskar, Anjor (Welthungerhilfe, 2008)
The results of the India State Hunger Index 2008 highlight the continued overall severity of the hunger situation in India, while revealing the variation in hunger across states within India. It is indeed alarming that not a single state in India is either low or moderate in terms of its index score; most states have a “serious” hunger problem, and one state, Madhya Pradesh, has an “extremely alarming” hunger problem. Although variation exists in index scores of the states, and hence in the ranking of Indian states in relation to other countries, few states perform well in relation to the GHI 2008. Even the best-performing Indian state, Punjab, lies below 33 other developing countries ranked by GHI. Even more alarming is the fact that the worst-performing states in India—Bihar, Jharkhand, and Madhya Pradesh—have index scores similar to countries that are precariously positioned on the GHI 2008 rankings. For instance, Bihar and Jharkhand rank lower than Zimbabwe and Haiti, whereas Madhya Pradesh falls between Ethiopia and Chad. Our analysis of the associations between the ISHI 2008 and state economic indicators shows that the relationship between poverty and hunger is largely as expected—greater ISHI 2008 scores are seen in poorer states, with a few exceptions. Outliers like Kerala, Orissa, and Punjab perform better on the ISHI 2008 than might be expected given their poverty levels, whereas Gujarat, Karnataka, and Madhya Pradesh perform worse. A closer examination of these states’ past and current investments in social protection, health, and nutrition programs can help inform the debate about policy instruments to protect populations against hunger even in the face of poverty. The lack of a clear relationship between state-level economic growth and hunger, taken along with the relationship between the ISHI 2008 and poverty and incomes, has a number of implications. First, economic growth is not necessarily associated with poverty reduction. Additionally, even if equitable economic growth improves food availability and access, it might not lead immediately to improvements in child nutrition and mortality, for which more direct investments are required to enable rapid reductions. Thus, in addition to wide-scale poverty alleviation, direct investments in improving food availability and access for poor households, as well as direct targeted nutrition and health interventions to improve nutrition and mortality outcomes for young children, will be needed to raise the ISHI scores and rankings of Indian states. Child underweight contributes more than either of the other two underlying variables to the GHI score for India and to the ISHI scores for almost all states in India. Tackling child undernutrition, therefore, is crucially important for all states in India. Achieving rapid reductions in child underweight, however, will require scaling up delivery of evidence-based nutrition and health interventions to all women of reproductive age, pregnant and lactating women, and children under the age of two years. Some economically strong states had rankings on the Nutrition Index that deteriorated when compared with the ISHI 2008, suggesting that it might be important for these states to invest in direct nutrition and poverty alleviation interventions even during sustained economic growth. The design and implementation of policies and programs to improve all three underlying dimensions of the ISHI will need to be strengthened and supported to ensure that hunger is reduced rapidly over time. Although strides are being made on the public health front to ensure sustained reductions in child mortality, improvements in child nutrition are not satisfactory in India. Nutrition programs in India are not effectively delivering evidence-based interventions at scale to vulnerable age groups that need to be reached to ensure rapid reductions in undernutrition. In conclusion, for Indian states to progress along the ISHI, and to ensure that ISHI scores for Indian states are more closely aligned with GHI scores of countries with comparable economic growth, investments will be needed to strengthen agriculture, improve overall food availability and access to all population segments, and to improve child nutrition and mortality outcomes.